Metal-dielectric phase transition of VO2 assisted broadband and high-efficiency bifunctional metasurface in the terahertz frequency: Metal-dielectric phase transition of VO2 assisted broadband and high-efficiency bifunctional metasurface - Minh, Nguyen Thi; Thu, Nguyen Thi Kim; Van, Nguyen Thi Hong; Tam, Nguyen Thi Minh; Thuong, Ho Thi Huyen; Tung, Phan Duy; Lam, Vu Dinh; Hoa, Nguyen Thi Quynh (Vietnam Journal of Science and Technology, 2022)
The integration of multiple varied functionalities into a single and compact EM-based device is greatly demanded in EM integration due to their miniaturized configurations. In this paper, a broadband and high-efficiency bifunctional metasurface employing vanadium dioxide (VO2) is proposed for the terahertz (THz) frequencies. Due to the dielectric-to-metal transition of VO2, the metasurface can be dynamically tuned from a reflecting surface to a broadband absorber under low-temperature conditions. When VO2 is in the dielectric phase, the designed metasurface shows excellent reflection (> 96 %) in a broad frequency range from 0.5 THz to 4.5 THz. Once VO2 is heated up and transited to its metal phase, the proposed metasurface structure efficiently absorbs normally incident EM waves in the frequency range of 1.29 THz to 3.26 THz with an average absorption of 94.3 %. Moreover, the high absorption characterization of the proposed metasurface is maintained with a wide incident angle and is polarization-insensitive due to its symmetric structure, which makes it suitable for THz applications.